Temperature effect on oxidative stress and egg quality‐related genes on post‐ovulatory eggs and ovary of red cusk‐eel (Genypterus chilensis). Issue 5 (26th January 2021) - Dettleff, Phillip; Zuloaga, Rodrigo; Fuentes, Marcia; Estrada, Juan M.; Molina, Alfredo; Valdés, Juan A.
Abstract: Red cusk‐eel ( Genypterus chilensis ) is a native species with potential for Chilean aquaculture diversification. However, no information exists on the effects of temperature on oxidative stress and eggs quality markers in post‐ovulatory eggs and ovary of this species. We determine that high and low temperature generate oxidative damage on post‐ovulatory eggs, with no effect on ovary. Temperature induces thermal stress markers expression on post‐ovulatory eggs, and modulates antioxidant and eggs quality markers on post‐ovulatory eggs and ovary, information to consider for quality evaluation in the red cusk‐eel management.